Amplification of a major membrane-bound DNA sequence of Bacillus subtilis. - Sargent, M G (1985)
A membrane-bound DNA sequence from Bacillus subtilis was subcloned into a plasmid which can replicate in Escherichia coli but not in B. subtilis. This plasmid hybridized with an 11-kilobase HindIII fragment which is the major particle-bound fragment in lysates treated with HindIII. The plasmid integrated into the B. subtilis chromosome at the region of homology, conferring chloramphenicol resistance on the recipient. The inserted resistance was mapped close to purA by using the generalized transducing phage AR9. In one chloramphenicol-resistant strain, the pMS31 region was repeated at least 20 times. A large proportion of the copies of the cloned region were present in the particle fraction, indicating that the capacity to bind this region of the chromosome was substantially in excess of the normal dose of the region. The structure of the particle-bound region was sensitive to ionic detergents and high salt concentrations but was not greatly affected by RNase or ethidium bromide. The basis of a specific DNA-membrane interaction can now be studied by using the amplified region, without the complications of sequences required for autonomous plasmid replication.